Expression of putative leukemia stem cell targets in genetically-defined acute myeloid leukemia subtypes. (December 2020) - Yanagisawa, Breann; Perkins, Brandy; Karantanos, Theodoros; Levis, Mark; Ghiaur, Gabriel; Smith, B. Douglas; Jones, Richard J.
Highlights: Most previously described putative leukemia stem cell targets are expressed across heterogeneous phenotypes of leukemia stem cells. CD123 and CLL-1 showed the greatest quantitative differences in expression between HSCs and LSCs. CD123 antibody was cytotoxic to all studied LSCs, but not normal HSCs or progentitors. Abstract: Although most acute myeloid leukemia (AML) patients achieve complete remissions, the majority still eventually relapse and die of their disease. Rare primitive leukemia cells, so-called leukemia stem cells (LSCs), represent one potential type of resistant cell subpopulation responsible for this dissociation between response and cure. Several LSC targets have been described, but there is limited evidence about their relative utility or that targeting any can prevent relapse. LSCs not only appear to be biologically heterogeneous, but the classic immunocompromised mouse transplantation model also has serious shortcomings as an LSC assay. Out data suggest that the most immature cell phenotype that can be identified within a patient's leukemia may be clinically relevant and represent the de facto LSC. Moreover, although phenotypically heterogeneous, these putative LSCs show consistent phenotypes within individual genetically defined groups. Using this LSC definition, we studied several previously described putative LSC targets, CD25, CD26, CD47, CD96, CD123, and CLL-1, and all were expressed across heterogeneous LSC phenotypes. In addition, with the exception of CD47, there was at most low expression of these targets on normal hematopoietic stem cells (HSCs). CD123 and CLL-1 demonstrated the greatest expression differences between putative LSCs and normal HSCs. Importantly, CD123 monoclonal antibodies were cytotoxic in vitro to putative LSCs from all AML subtypes, while showing limited to no toxicity against normal HSCs and hematopoietic progenitors. Since minimal residual disease appears to be a more homogeneous population of cells responsible for relapse, targeting CD123 in this setting may be most effective.